Iodine and Selenium Consumption and Its Relationship with Iodine Status of School Children in Endemic and Non Endemic Coastal Areas - . Rimbawan; Ali Khomsan; Dadang Sukandar; Sri Sumarmi; Sri Wahyu Angga Dewi (Media Gizi dan Keluarga, 2000)
The specific objectives of this research were to study food consumption; iodine and selenium content of foodstuffs; intake of nutrients (energy, protein, vitamin A, iodine and selenium); and status of iodine among elementary school children living in coastal areas of Pasuruan District, East Java Province. The study was also purposed to observe the correlation between nutrients consumption and iodine status. Kalirejo Village was chosen purposively to represent a non endemic area of IDD in which the Total Goitre Rate (TGR) was 45%, while Tambak Lekok Village represented a non endemic area of IDD with no cases of goiter signs. Sixty elementary school children in each area were randomly selected as samples to whom 24 hours food consumption recall and early morning urine were collected. Urinary Excretion of Iodine (UEI) was analysed from each sample to measure the status of iodine. Statistical method called t-test was applied to judge any difference between the data of consumption, nutrient adequacies, UEI level (iodine status) in both areas. Correlation between variables was also examined statistically by multiple linier regression test. For all kind of food of animal origins, samples living in IDD-non endemic area consumed more in term of quantity than that in IDD-endemic area. The adequacy levels for energy, protein, vitamin A, iodine and selenium in IDD-endemic area were 89.61%, 234.24%, 269.92%, 23.33% and 78.79% respectively; while those in IDD-non endemic area were 107.59%, 208.68%, 151.99%, 103.07% and 239.18% respectively. No significant (p>0.05) difference was observed between data of nutrients consumption, energy adequacy level and protein adequacy level obtained from an IDD-endemic area and those obtained from non endemic area. In contrast, consumption and adequacy level of vitamin A, iodine and selenium of IDD-endemic area were significantly different from those observed in IDD-non endemic area. Generally, iodine and selenium content of foodstuffs obtained from IDD-endemic area were lower than those from IDD-non endemic area. UEI of samples living in IDD-endemic area were 108,50 u/l. These was significantly different from those living in with non endemic area, which were 192 u/l. Consumption of energy, protein and vitamin A showed no significant influence on iodine status. Iodine and selenium consumption were very significantly influenced by iodine status. Iodine status was very significantly influenced by iodine consumption.Keywords: iodine, selenium, chool children